Α7-Nicotine acetylcholine receptor mediated nicotine induced cell survival and cisplatin resistance in oral cancer. (March 2020) - Hsu, Chia-Chen; Tsai, Kuo-Yang; Su, Yu-Fu; Chien, Chu-Yen; Chen, Ying-Chen; Wu, Yu-Chiao; Liu, Shyun-Yeu; Shieh, Yi- Shing
Highlights: Nicotine enhanced cell survival and drug resistance of OSCC cells by α7-nAChRs. Blocking α7-nAChRs may increase chemosensitivity in patients. Bcl-2 was involved in nicotine-induced cisplatin resistance. Abstract: Objective: To investigate the effect of nicotine on cell survival and cisplatin resistance in oral cancer and the possible involvement of α7-nicotinic acetylcholine receptors (α7-nAChRs). Design: The effects of nicotine on cell survival and cisplatin-induced apoptosis were assessed. Knockdown of α7-nAChRs by short hairpin RNA and the specific antagonist methyllycaconitine (MLA) was used to examine the involvement of α7-nAChRs in modulating the effects of nicotine. Apoptosis signal molecules were examined in nicotine- and cisplatin-treated cells. Results: Nicotine increased the survival of the oral cancer cells YD8 and OEC-M1 in a dose- and time-dependent manner. Nicotine treatment accelerated cell cycle progression in the oral cancer cells, and significantly reduced cisplatin-induced cell apoptosis. In the α7-nAChR-silenced cells, the prosurvival effect of nicotine in the cisplatin-treated cells was attenuated. Co-treatment of cisplatin and nicotine attenuated the effect of cisplatin on Bcl-2 expression. In addition, the effect of nicotine on cell survival under cisplatin treatment was attenuated with the addition of the Bcl-2 inhibitor ABT-737. Conclusions: Treating oral cancer cells with nicotine increased cell survival and cisplatin resistance, in which α7-nAChRs were involved.